PEMBERIAN INKLUSI SISTEM PENJURNALAN PADA PERUSAHAAN JASA BAGI SEKOLAH KATOLIK ST. KRISTOFORUS I JAKARTA - Yustina Peniyanti Jap (PROSIDING SERINA, 2021)
This Community Service Activity (PKM) is one of the manifestations of the Tri Dharma of Higher Education which can provide benefits to the community, especially high school students at Catholic School. St Kristoforus I, with located ed in West Jakarta. This activity is carried out through presentations, discussions, discussions about the journaling system for transactions at service companies. We see that in the Accounting Subject learning system,  Catholic School,  St. Kristoforus  I, need a Module. Therefore, the module produced from this Community Service is expected to be useful in the teaching system of Accounting Subjects at Catholic School, ST Kristoforus I. The implementation of accounting learning becomes more focused and has better stages. With the module, of course, it can help students understand the accounting cycle and bookkeeping system more comprehensively. As for Tarumanagara University, especially the Faculty of Economics and Business, it is a role to support the introduction of the accounting program of the Faculty of Economics and Business majoring in accounting. So that St. Kristoforus High School students who want to continue to study FEB majoring in Accounting have no doubts. In addition, at the same time to foster good relations with educational institutions at the high school level at St. Kristoforus I.